Effect of oxidation of catalytically active silicon-based electrodes on water decomposition - Primachenko, V.E.; Serba, O.A.; Chernobai, V.A.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
In this work, we continue to study the revealed phenomenon of current
creation in the electrochemical system with distilled water during its decomposition
without any applied external voltage. Investigated are catalytically active (to decompose
water) electrodes based on silicon with modified surface (due to lapping, texturing,
doping with palladium, creation of silicides) before and after thermooxidizing for 1 hour
in dry oxygen at 850 ºC. Also performed are investigations of time dependences for the
current between silicon electrodes and counter-electrodes made of Al, Pt, Yb when using
the circuit with the external voltage V₀ = ± 9.7 V. Analyzed are the results obtained and
prospects for a further study.